2003
DOI: 10.1016/s0003-2697(02)00710-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased resonance energy transfer between fluorophores bound to DNA in proximity to metallic silver particles

Abstract: We examined the effects of metallic silver particles on resonance energy transfer (RET) between fluorophores covalently bound to DNA. A coumarin donor and a Cy3 acceptor were positioned at opposite ends of a 23-bp double helical DNA oligomer. In the absence of silver particles the extent of RET is near 9%, consistent with a Forster distance R 0 near 50 Å and a donor to acceptor distance near 75 Å. The transfer efficiency increased when the solution of AMCA-DNA-Cy3 was placed between two quartz plates coated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 33 publications
0
40
0
3
Order By: Relevance
“…Lakowicz and co-workers have reported a number of surface effects on fluorescence, including enhanced intrinsic fluorescence from unlabeled DNA, 41 improved photostability, 42 and increased resonant energy transfer between DNA-bound molecular donors and acceptors. 43 This group has also reported increased apparent quantum yields and decreased lifetimes for Cy3-and Cy5-labeled dsDNA adsorbed nonspecifically onto Ag particles. 44 The kinetics of labeled complementary strands to surfacebound probe DNAs have been followed in real time by both surface plasmon field enhanced 21 and epi-illumination 45,46 fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…Lakowicz and co-workers have reported a number of surface effects on fluorescence, including enhanced intrinsic fluorescence from unlabeled DNA, 41 improved photostability, 42 and increased resonant energy transfer between DNA-bound molecular donors and acceptors. 43 This group has also reported increased apparent quantum yields and decreased lifetimes for Cy3-and Cy5-labeled dsDNA adsorbed nonspecifically onto Ag particles. 44 The kinetics of labeled complementary strands to surfacebound probe DNAs have been followed in real time by both surface plasmon field enhanced 21 and epi-illumination 45,46 fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…In the past years we have taken a different approach to create improved probes, this being the use of metallic nanoparticles [1][2][3]. Ensemble experiments have revealed that proximity to silver particles could increase the intensity and photostability of fluorphores [4][5][6][7][8][9]. This effect is due to the through-space nearfield interaction between the fluorphore and surface plasmons on the metals.…”
mentioning
confidence: 99%
“…Therefore, we examined the widely used fluorescent probe Cy5 near SIFs. These films consist of sub-wavelength-size silver particles on a glass surface [4,5]. Our single-molecule experiments of this system reveal both the spectral changes due to the metal particles and the heterogeniety due to a range of fluorophore-metal distances.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] Generally, the emission energy level of a donor molecule coincides with the absorption energy level of the acceptor, in the DNA mediated excited energy transfer, thus, is resonance energy transfer (RET) type in its nature. The excited energy of 4',6-diamidino-2-phenylindole (DAPI, Figure 1) has been reported to transfer to DNA intercalating [Ru (1,10-…”
Section: -19mentioning
confidence: 99%